2022
DOI: 10.3390/biomedicines10071487
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Liver Fibrosis in Patients with Nonalcoholic Fatty Liver Disease and Type 2 Diabetes Mellitus

Abstract: Liver fibrosis is a key pathophysiology process in chronic liver disease. It is still unclear whether the impact of liver fibrosis is not fully realized in type 2 diabetes mellitus (T2D) patients with nonalcoholic fatty liver disease (NAFLD), and the factors affecting nonalcoholic steatohepatitis (NASH) or liver stiffness also remain unclear. The aim of this study was to evaluate the determinants of liver fibrosis and in T2D patients with NAFLD. Liver fibrosis and steatosis were measured using transient elasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
(70 reference statements)
1
3
0
Order By: Relevance
“…After the onset of menopause, the incidence is comparable. The same higher incidence for the male gender, but lower compared to our study (51.8%), was present in a Chinese study that investigated the factors of progression to fibrosis in patients with NAFLD and T2DM [35]. Regarding the mean age of the patients, it was higher in patients with HS and T2DM compared to the group of patients with NASH and T2DM.…”
Section: Discussionsupporting
confidence: 77%
“…After the onset of menopause, the incidence is comparable. The same higher incidence for the male gender, but lower compared to our study (51.8%), was present in a Chinese study that investigated the factors of progression to fibrosis in patients with NAFLD and T2DM [35]. Regarding the mean age of the patients, it was higher in patients with HS and T2DM compared to the group of patients with NASH and T2DM.…”
Section: Discussionsupporting
confidence: 77%
“… 11–13 Higher levels of liver enzymes are independently associated with LF. 14–16 Other risk factors include age, 17 , 18 dyslipidemia, 19 hypertension 20 and race. 11 , 21 To date, there are few studies to explore the relevant factors of LF in Chinese diabetes patients combined with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have confirmed that one of the key risk factors for the development of liver fibrosis is liver aging, so we also established a transcriptomic signature that could be used to assess the degree of liver aging [28][29][30]. To construct a liver aging-related transcriptomic signature (Liver aging signature), we included 4 transcriptomic datasets comparing the livers of older individuals with younger individuals by searching the GEO database, including GSE61260, GSE107037, GSE133815 and GSE183915.…”
Section: Establishment and Validation Of Key Transcriptomic Signaturesmentioning
confidence: 99%